Gene Regulation - Gurbachan S. Miglani (Narosa Publishing House, 2013)
GENE REGULATION deals with the molecular mechanisms of regulation of gene expression in viruses, bacteria and eukaryotes. Role of epigenetic modifications in gene regulation is dealt with in detail. While molecular basis of development and evolution in light of the recent discoveries finds a special mention, in the last chapter, modification and modulation of gene expression and exploitation of gene regulation has been discussed. The Genetic material and gene expression have been described only very briefly in the first chapter. Gene Regulation is primarily designed as a text book for senior undergraduate and post-graduate students. Undergraduate and graduate students, teachers and researchers in any discipline of life sciences, agricultural sciences, medicine, and biotechnology in all the conventional and agricultural universities, research institutes, molecular genetics and biotechnology companies/colleges/ institutes/schools all over the world will also find it useful as a reference book.